Peningkatan Kemampuan Membaca Huruf Hijaiyah Melalui Media Papan Pintar Kelompok A di RA Perwanida Kandangan - Shidah, Mafaizatu Al Mustar; Rachmah, Laela Lutfiana; Shohwan, Arif Muzayin; farantika, dessy (Journal of Childhood Education, Development and Parenting, 2023)
Learning media is a tool or means used to convey learning material effectively so that it can foster students' enthusiasm for learning in order to achieve learning goals. However, in reality at RA Perwanida Kandangan learning to recognize hijaiyah letters in group A still uses less innovative learning media, namely directly using iqra' supporting books. The media seems less attractive in the eyes of children. Children become lazy, bored, feel forced, and less motivated in learning. So that the ability of children to recognize hijaiyah letters in group A is still low. Hijaiyah smart board media was created as an alternative problem solving in learning to recognize hijaiyah letters. The purpose of this study was to increase the ability to recognize hijaiyah letters in group A at RA Perwanida Kandangan. This type of research is Classroom Action Research (CAR). This study consisted of three cycles consisting of four stages, namely: planning, acting, observing, and reflecting. This research was conducted at RA Perwanida Kandangan by taking group A subjects aged 4-5 years, totaling 15 children. The results of the research and assessment of PTK stated that there was an increase in the ability to read hijaiyah letters through smart board media that had been designed in group A at RA Perwanida Kandangan namely: before the action/pre-cycle the ability to read hijaiyah letters was stated as BB of 53.33%, MB of 33.33%, BSH of 13.33%, and BSB of 0%, in cycle I it was stated that BB was 15.55%, MB was 64.44%, BSH was 20% , and BSB 0%. In cycle II, the results of BB were 0%, MB were 22.22%, BSH were 51.11%, and BSH were 26.66%, and in cycle III it increased as expected by obtaining BB results of 0%, MB of 4.44%, BSH of 57.77%, and BSH of 37.77%. From the results of this study it can be concluded that there has been an increase in the ability to read hijaiyah letters through smart board media at RA Perwanida Kandangan